Effect of vaccination on the use of antimicrobial agents: a systematic literature review. (17th August 2020) - Doherty, T. Mark; Hausdorff, William P.; Kristinsson, Karl G.
Abstract: Background: Antimicrobial resistance is a growing global health threat. To preserve the effectiveness of antimicrobials, it is important to reduce demand for antimicrobials. Objectives: The objective of the study was to screen the existing peer-reviewed literature to identify articles that addressed the potential impact of influenza or Pneumococcus vaccination on antibiotic usage. Data sources: PubMed, Embase Study eligibility criteria: Clinical studies where antimicrobial prescribing was assessed in both vaccinated and unvaccinated populations. Participants and interventions: All patient populations were included (infants, children, adults and elderly), where the effects of the intervention (vaccination) was assessed Results: We identified unique 3638 publications, of which 26 were judged to be of sufficiently high quality to allow the calculation of the potential impact of vaccination. Of these studies 23/26 found a significant reduction in antibiotic use by at least one of the parameters assessed. Limitations: Different measures used to define anti-microbial use, studies typically focus on specific risk groups and most studies are from high-income countries. Conclusions and implications of key findings: Despite the limitations of the review, the evidence indicates that improved coverage with existing vaccines may significantly reduce antimicrobial demand. This suggests it may be a valuable tool for antimicrobial stewardship. Key messages: While vaccines against a number of pathogens have been studied for their ability to reduce antimicrobial use, currently only vaccination against influenza or pneumococcus has generated sufficient data for analysis Vaccination against either influenza or pneumococcus significantly reduced overall antimicrobial prescribing rates, both in vaccinated individuals and at a population level Maintaining and expanding vaccination coverage thus appears to be a key tool for antimicrobial stewardship